KEMAMPUAN Pseudomonas aeruginosa PAO1 DALAM SERAPAN LOGAM BESI (Fe) PADA LIMBAH LINDI DI TPA GAMPONG JAWA KOTA BANDA ACEH - Diannita Harahap; Zakirul Rahmad; Husnawati Yahya; Juliansyah Harahap (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2023)
Leachate is a liquid containing hazardous materials such as metal Iron (Fe). One method that can be used to reduce Fe levels in leachate is using the bioremediation method. This study aimed to determine the absorption ability of Pseudomonas aeruginosa bacteria in remediating Fe as well as the physical and chemical characteristics of leachate such as COD, TSS, and pH before and after using P. aeruginosa. This study used an experimental method of four treatments and three replications. The concentration of bacteria used was 108 CFU/ml with ex-situ contact times of 0, 10, 20, and 30 hours. The results showed that the highest decrease in Fe, COD, TSS, and pH occurred at 30 hours. The Fe value can be reduced to 4.45 mg/L with an absorption effectiveness of 38.19%; the initial COD value of 1.432 mg/L decreased to 1.301 mg/L. In addition, the TSS value decreased to 213 mg/L from the initial level of 223 mg/L and the highest pH decreased, namely 9.6 to 8.1. The uptake of P. aeruginosa bacteria is good in reducing acceptable levels of Fe and pH.